Kimito Funatsu - The Driving Force of Chemoinformatics in Japan - Gasteiger, Johann (Journal of Computer Aided Chemistry, 2019)
The achievements of Professor Kimito Funatsu for the development of chemoinformatics in Japan are briefly summarized Furthermore, some aspects of the collaboration of this author with Kimito Funatsu are discussed.
CRIS-Team WoS Importer:2021-01-01